Jesus as a Good Shepherd in John 10:11: Spiritual Leadership in Indonesian Context - Paulus Eppang; Inge Nuraini; Hartanto Hartanto (Davar : Jurnal Teologi, 2026)
Abstract The metaphor of Jesus as the Good Shepherd in John 10:11 has long shaped Christian understandings of spiritual leadership, yet its relevance to contemporary pastoral leadership in Indonesia has received limited scholarly attention. This study aimed to examine the concept of the shepherd as a spiritual leader by drawing on Jesus' example and exploring its application within the Indonesian Christian community. The study was situated within the context of Indonesian churches. It employed exegetical and hermeneutical approaches, integrating biblical and literary analysis with observations from Indonesian scholarship and interviews with church pastors. The findings showed that effective spiritual leadership reflected Christ's example through sacrificial service, close pastoral relationships, moral integrity, unity, and care for the flock. The study concluded that the Good Shepherd model remained highly relevant for pastoral leadership in Indonesia and contributed a contextual biblical framework for developing Christ-centred spiritual leadership in contemporary Christian communities.   Keywords: good Shepherd, hermeneutics, Indonesian Christianity, John 10:11, spiritual leadership